(untitled) (Patan Pragya, 2022)
The article is based on the local elections in 2017 which is a historic milestone for the country. Local elections were held after almost two decades. They became a key vessel for acting upon the Constitutional obligation toward gender and social inclusion in the government and ending the political impasse that beset the country for many years. The article focuses on two objectives: first to identify the priorities of local elected women’s needs on capacity and skills and to identify the interventions that could be designed to help support the elected women in the different local governments of Jhapa and Lalitpur Districts. The paper is based on descriptive and analytical types of research design as well as nature of data both primary and secondary sources. It has used both quantitative and qualitative methods of data collection and deductive and inductive approaches to the analysis of the data. Information is gathered and assessed on the basis of capacity and skills of elected women. The data are analysed using the Excel spread program on the computer and are calculated in frequency distribution and percentage. Data are carefully analysed and interpreted for generalization. Gender inclusion in local government is gradually increasing in development sector of local areas. The findings and analysis of the study are largely indicative given that the study sample is limited but more so because the present situation on the ground is dynamic. Yet, it cannot be denied that there is palpable excitement and optimism amongst elected women representatives to be active participants in Nepal’s evolving governance structures. Tempering the optimism with a realistic assessment of the challenges and work on hand is needed. Building capacities and a supportive environment for women’s leadership in local governance in the context of federalism in Nepal is needed.